1982
DOI: 10.1128/jb.151.2.783-787.1982
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa mutants altered in their sensitivity to the effect of iron on toxin A or elastase yields

Abstract: Iron affects yields of toxin A, alkaline protease, elastase, pyochelin, and pyoverdin in Pseudomonas aeruginosa. Mutants of P. aeruginosa PAO1 resistant to the effect of iron on toxin (toxC) or elastase (elaC) yields were isolated. Two types of mutants were isolated: iron transport and iron regulatory mutants. The toxC regulatory mutants produced toxin A in medium containing iron; however, yields of elastase and alkaline protease remained sensitive to regulation by iron. The elaC regulatory mutants were resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

1984
1984
1999
1999

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…Thus, it appears that, for sodA , the QS regulatory system is integrated with iron-sensitive circuitry that activates transcription of the operon regardless of growth phase (Hassett et al, 1996). We note that this is also consistent with the effects of iron availability on production of the P. aeruginosa virulence factors elastase, exotoxin A and pyoverdine (Sokol et al, 1982).…”
Section: Mn-sodsupporting
confidence: 76%
“…Thus, it appears that, for sodA , the QS regulatory system is integrated with iron-sensitive circuitry that activates transcription of the operon regardless of growth phase (Hassett et al, 1996). We note that this is also consistent with the effects of iron availability on production of the P. aeruginosa virulence factors elastase, exotoxin A and pyoverdine (Sokol et al, 1982).…”
Section: Mn-sodsupporting
confidence: 76%
“…S, fyp/i/mur/iym might use the limitation of free iron as a signal for induction of virulence genes. It has been shown that haemolysin induction in Listeria monocytogenes (Cowart, 1987) or exotoxin A induction in Pseudomonas aeruginosa (Sokol et al,. 1982) are regulated by free iron.…”
Section: Discussionmentioning
confidence: 99%
“…Pyochelin is a salicylic acid-substituted cysteinyl peptide siderophore [3]. P. aeruginosa and P. fluorescens also produce pyoverdin which has been shown to have siderophore activity [4,5]. A third mechanism for iron transport from ferric, citrate has also been described in P. aeruginosa [6].…”
Section: Introductionmentioning
confidence: 99%